Length of Barrett's oesophagus: an important factor in the development of dysplasia and adenocarcinoma. Issue 9 (September 1992) - Iftikhar, S Y; James, P D; Steele, R J; Hardcastle, J D; Atkinson, M
Abstract : In a 15 year prospective study of endoscopic surveillance of columnar lined oesophagus, 102 patients with a mean follow up of 54 (12.5) months and total follow up of 462 years have been evaluated. Of all the sets of biopsies taken, 59 in 21 patients were found to exhibit dysplasia or carcinoma. Four male patients had carcinoma of the oesophagus, indicating a 30 times increased risk of development of adenocarcinoma in columnar lined oesophagus. The length of columnar lined oesophagus in subjects with dysplasia was significantly longer as compared with the whole group (p = 0.01) and when compared with the patients without dysplasia (p = 0.005). None of the patients with dysplasia had a columnar lined oesophagus of less than 8 cm. Length of columnar lined oesophagus therefore seems to be a significant risk factor in the development of dysplasia and subsequent carcinoma and intensive follow up of patients with columnar lined oesophagus greater than 8 cm in length is recommended.